The Identity of Fuegian and Patagonian “Dogs” Among Indigenous Peoples in Southernmost South America - Castro-Morales, S (BioMed Central Ltd, 2023)
Background: By using a historical approach we attempt to answer the question of whether the “dogs” of Fuegian and Patagonian peoples are a domesticated dog (Canis lupus familiaris) or a tamed or domesticated Culpeo “fox” (Lycalopex culpaeus), or a cross breed. Methods and results: We reviewed historical chronicles and current scientific papers, and clarified several rather confusing concepts, providing disambiguation for terms such as Magellanic region, Patagonia, and Tierra del Fuego; Fuegian and Patagonian peoples; and Fuegian and Patagonian dogs. We conclude that these dogs belong to two different canid varieties: The smaller domestic dog typical of the “canoe-indians” (Chonos, Kawesqar, and Yahgan peoples) and the larger tamed or domesticated Culpeo “fox" typical of the “foot indians” (Aonikenk, Manek enk, and Selk’nam peoples, thus proposing the use of Fuegian and Patagonian dog, respectively. Discussion: We think that the original Fuegian dog was indeed a Canis lupus familiaris brought along by the natives after the Bering’s crossing and that the Patagonian dog was a tame Culpeo fox Lycalopex culpaeus, which was progressively replaced by the more gregarious, human friendly, and colorful domestic dogs brought by European explorers, adventurers, colonizers, and settlers of Patagonia and Tierra del Fuego during the mid to late 1800s. The possibility that the Patagonian dog was a cross between domestic dog and Culpeo “fox” cannot be ruled out, but the only specimen genetically analyzed was closest to being the latter and not a hybrid. © 2023, The Author(s).